A statistical analysis of high-performance prosthetic isogrid composite tubes using response surface method. Issue 6 (26th November 2020) - Francisco, Matheus; Roque, Lucas; Pereira, João; Machado, Susiane; da Cunha Jr, Sebastião Simões; Gomes, Guilherme Ferreira
Abstract : Purpose: This study aims to address a deep statistical analysis on transtibial prostheses made of composite isogrid carbon/epoxy structure. Design/methodology/approach: For the methodological procedure, an experimental arrangement was created using design of experiments, and the response surface methodology (RSM) was used. The RSM was obtained from the decision variables of the isogrid model, which consists of angle, circular width and helical width. All modeling was performed numerically using the finite element method. Findings: Results obtained through analysis of variance (ANOVA) indicated the sensitivity of each decision variable (manufacture) in the mechanical responses. The results obtained in this study provide a starting point in formulating optimization problems for researchers and engineers. Originality/value: A noteworthy thing about structural analysis and structural optimization is that some parameters and decision variables are more significant than others in certain responses (Major et al., 2011). Knowing the sensitivity of these parameters is essential for the correct formulation of an optimization problem. To handle these obstacles, design of experiments and ANOVA are used to solve and obtain the main effects on the structural performance. Nevertheless, to the best of the authors' knowledge, very few efforts have been devoted to the development to show the factors that influence the various responses of a lower limb prosthesis isogrid tube.